2020
DOI: 10.1097/pec.0000000000001997
|View full text |Cite
|
Sign up to set email alerts
|

Does Point-of-Care Gastric Ultrasound Correlate With Reported Fasting Time?

Abstract: Objective: Traditionally, patient-reported fasting time has been the primary objective presedation measure of aspiration risk. Recently, gastric ultrasound has been used to assess gastric volume for the determination of aspiration risk in patients undergoing anesthesia in the operative setting. We sought to determine the correlation of gastric volume estimated by point-of-care ultrasound (POCUS) to reported fasting time. Methods:We included children 4 to 18 years of age who presented with an acute traumatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In our cohort of children with acute appendicitis, gastric contents were not associated with the duration of fasting or abdominal pain. Recent ultrasound studies have likewise reported a poor correlation between gastric contents and fasting time in acutely ill children, both in the emergency department [21][22][23] and in the operating theatre [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort of children with acute appendicitis, gastric contents were not associated with the duration of fasting or abdominal pain. Recent ultrasound studies have likewise reported a poor correlation between gastric contents and fasting time in acutely ill children, both in the emergency department [21][22][23] and in the operating theatre [9].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort of children with acute appendicitis, gastric contents were not associated with the duration of fasting or abdominal pain. Recent ultrasound studies have likewise reported a poor correlation between gastric contents and fasting time in acutely ill children, both in the emergency department [21–23] and in the operating theatre [9]. However, other potential risk‐factors such as the presence of local complications and pre‐operative administration of opioid analgesics could not be analysed using multivariable regression given the limited numbers of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fasting children planned for elective surgery, gastric content volume was low ( 79 ) and the percentage of “stomachs at risk of aspiration” was 1% ( 2 ), but in the emergency setting, Gagey et al and Evain et al reported the incidence of full stomach to be between 51 and 37%, respectively ( 27 , 31 , 32 ). In children, fasting for more than 6 h admitted to the ED and requiring procedural sedation, 18–69% of these had a full stomach ( 6 , 37 , 41 ). Gagey et al reported that an ultrasound-guided anesthetic strategy led to an 85% appropriate induction sequence technique compared to 49% after clinical assessment alone in non-elective children ( 31 ).…”
Section: Gastric Emptyingmentioning
confidence: 99%
“…[47][48][49][50][51] Additionally, gastric POCUS has been used to assess stomach content in critically-ill ICU patients 52,53 and more recently in emergency department patients. [54][55][56][57][58] Importantly, although the Perlas Model is now being used to evaluate gastric content in these settings, the applicability and implication of the model's assigned "risk" categories outside of the anesthesia arena are entirely unknown, although for the sake of consistency with prior literature, we will continue to use the model's terminology.…”
mentioning
confidence: 99%